Public perception towards service quality between Malaysia Airlines and Air Asia / Nor Afifa Yusop & Zarith Eleena Za'aba - Yusop, Nor Afifa; Za'aba, Zarith Eleena (2015)
This chapter focuses the background of the study which is on the public perception towards service quality between the Malaysia Airlines and Airasia. It also emphasize on the definition of the public perception and the importance of the service quality in influencing the public perception. Section 1.1 discusses the background of the study, section 1.2 explain the problem statement and section 1.3 states the research objective. Section 1.4 state the research question and section 1.5 is on the information regarding the scope the study. 1.6 explain the significant of the study and lastly section 1.7 is about the definition of terms and concept.